2023
DOI: 10.2196/42637
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Paper and Electronic Trail Making Tests for Automatic Analysis of Cognitive Impairment: Development and Validation Study

Abstract: Background Computer-aided detection, used in the screening and diagnosing of cognitive impairment, provides an objective, valid, and convenient assessment. Particularly, digital sensor technology is a promising detection method. Objective This study aimed to develop and validate a novel Trail Making Test (TMT) using a combination of paper and electronic devices. Methods This study included community-dwelling… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(49 reference statements)
1
1
0
Order By: Relevance
“…In our research, we discovered a negative correlation between the amount of two-handed coverage and MoCA-BJ scores. This finding aligns with previous studies [ 35 , 36 ], Dahdal executed the Motor Performance Series (MLS) to analyze fine hand movements and found that Parkinson’s patients with MCI had poorer dynamic stability compared to those without MCI [ 37 ]. An important feature of human fine motor is the minimal jerk, which represents a swing and pause throughout a continuous movement [ 17 ], cognitive functions play a crucial role in the control of the jerk.…”
Section: Discussionsupporting
confidence: 91%
“…In our research, we discovered a negative correlation between the amount of two-handed coverage and MoCA-BJ scores. This finding aligns with previous studies [ 35 , 36 ], Dahdal executed the Motor Performance Series (MLS) to analyze fine hand movements and found that Parkinson’s patients with MCI had poorer dynamic stability compared to those without MCI [ 37 ]. An important feature of human fine motor is the minimal jerk, which represents a swing and pause throughout a continuous movement [ 17 ], cognitive functions play a crucial role in the control of the jerk.…”
Section: Discussionsupporting
confidence: 91%
“…This analysis considered an expected effect size of 0.3, a significance level of .05, and a statistical power of 0.8, requiring at least 82 participants per group [37]. Similar research in the field also informed our sample size, which typically used participant numbers within this range for comparable outcomes [38][39][40][41].…”
Section: Experimental Participants and Proceduresmentioning
confidence: 99%